TECHNOLOGIES-SUPPORTED COLLABORATIVE PROBLEM-SOLVING LEARNING MODEL FOR FOREIGN LANGUAGE LEARNING BASED ON CASES AND PROJECTS - Al Adawiyah, Aisyiah; Syamsul Arifin, Akbar (JURNAL EDUSCIENCE, 2025)
Purpose—This research aims to develop standardized learning steps by applying technology to enhance student interactivity, improve learners’ communication skills, and address challenges of student engagement in foreign language learning.Methodology—The development process follows four stages: 1) preliminary research, 2) model development planning, 3) model validation, evaluation, and revision, and 4) model implementation. A qualitative approach is employed to gain insights into applying the developed model in classroom learning.Findings—The small-scale trial in the Grammaire Pré-Avancé course shows that students learn autonomy through group work that involves searching for references and improving their understanding of the discussed material. Specifically, the model developed enhances learners’ digital literacy, critical thinking skills, and language proficiency in both receptive and productive aspects.Significance—The research underscores the potential benefits of integrating technology with case methods and project-based learning. It can significantly boost digital literacy and critical thinking in foreign language learning and improve long-term language skills. Keywords:Learning model, Foreign language, Technologies-supported collaborative problem-solving